Cambrian trilobite biostratigraphy and its role in developing an integrated history of the Earth system. (28th March 2017) - Babcock, Loren E.; Peng, Shanchi; Ahlberg, Per
Abstract : One of the principal biostratigraphical tools used in the lower Palaeozoic, and especially the Cambrian System, is trilobites. Historically, both polymerids and agnostoids have commonly been included as 'trilobite' groups, although currently the question of whether they comprise a monophyletic group or are polyphyletic is unsettled. Beginning in the late 1800s, the base of the Cambrian System was marked by the lowest occurrence of olenelline trilobites. Discovery of a rich pre‐trilobite metazoan record in the mid‐1900s led to significant modification of that concept, but polymerids and especially agnostoids still rank among the leading biostratigraphical and chronostratigraphical guides through much of the Cambrian. Chronostratigraphical sub‐division of the trilobite‐bearing part of the Cambrian System derives largely from biostratigraphical, ecological and evolutionary concepts about agnostoids and polymerids introduced in the 1940s to 1970s by A.H. Westergård, A.R. Palmer and R.A. Robison. Westergård introduced a zonation for Scandinavia that was largely based on agnostoids. Palmer explained the distribution of Cambrian trilobite faunas in terms of restricted and unrestricted access to open oceans. Together, these ideas coalesced in Robison's recognition of separate zonation schemes for restricted‐shelf polymerids, open‐shelf polymerids and open‐shelf (cosmopolitan) agnostoids. Palmer also introduced the concept of biomeres, which placed sharp limits on biostratigraphical intervals recognizable from trilobites. Global correlation in the upper half of the Cambrian today depends to a large extent on the ranges of agnostoids and some polymerids characteristic of open‐shelf to slope areas, ones that facilitate identification of precise intercontinental tie points. Agnostoid and polymerid biostratigraphy is now being integrated with information about coastal onlap and eustatic sea‐level history, geochemical cycling and other data to provide a more complete understanding of the early Palaeozoic biosphere and its complex physico‐chemical context.